PERENCANAAN GEOMETRIK DAN TEBAL PERKERASAN KAKU (RIGID PAVEMENT) PADA JALAN KELOMPOK TANI MELAMBANG KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - HAKIM, LUKMAN (KURVA S JURNAL MAHASISWA, 2018)
Loa Tebu is one of the villages in Tenggarong District, Kutai Kartanegara Regency. Seen from the geographical area, Loa Tebu has an area of Â± 52 Km2 , most of the area is plantations and food self-help. Looking at the plantation sector and food self-sufficiency in the area as supporting the regional economy requires good and easily accessible road access. Plan the geometric path, design the thickness of rigid pavement and detail the cost budget with the aim of getting results in accordance with applicable standards. In planning this road using the Bina Marga method as a basis for geometric planning, pavement thickness and budget plan. The data needed in planning the road, namely the topographic map used in the geometric calculation of the road, the average daily cross (LHR) is used to determine the road class and CBR (California Bearing Ratio) to determine the thickness of the pavement. After the geometric and thick calculation of pavement, the required budget can be detailed. From the LHR data, the class III Local Secondary Road class was obtained. In geometric calculations the road obtained 29 bend types, 33 vertical curvature types and 30610 m3 soil excavation volumes 1056 m3 of landfill volume. From the results of the calculation of rigid pavement thickness obtained 18 cm concrete thickness with the quality of K-250, the thickness of the bottom foundation layer is 12.5 cm aggregate class B. From the results of fatigue analysis and repetition of the obtained permit value of small value (FRT) then alternative things can conducted by temperori using a class B aggregate with a thickness of 12.5 cm obtained from the results of effective soil CBR. Budget plan required costs Rp. 12,005,368,000.00. From the results of the budget plan for the cost of cement concrete which is relatively large cost, by using temperori method using class B aggregate only requires a budget of Rp.3,341,513000.00 as an alternative and cost savings. In geometric planning required valid measurement data to determine bend design and slope in accordance with specifications. Before determining the thickness of the pavement it is necessary to investigate the carrying capacity of the soil which is then processed into CBR as a basis for determining the thickness of the pavement. In the details to determine the cost budget, the things that need to be known, namely where the location of the material obtained and the condition of the field, it affects the making of the budget, because the material and equipment needs must be taken into account with the planned field conditions.